1991
DOI: 10.1111/j.1558-5646.1991.tb04342.x
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Stiffness Allometries of Angiosperm and Fern Petioles and Rachises: Evidence for Biomechanical Convergence

Abstract: Abstract.-Evidence for convergence in biomechanical and anatomical features of leaves (elastic modulus E, second moment of area I, taper of petioles, the longitudinal distribution of petiolar and laminar weight, and volumes oftissues) is presented based on a survey of22 species (distributed among dicots, monocots, and ferns). In general, regardless of taxonomic affinity, petioles were found to be mechanically constructed in one of two ways: Type I petioles-as cantilevered, endloaded beams with relatively unifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 25 publications
3
18
0
Order By: Relevance
“…Thus, changes in the thickness of foliage elements with irradiance were the primary determinants of modifications in EI. Ample evidence from previous studies demonstrates that petiole flexural stiffness scales positively with lamina load and petiole length, but also that both E and I may depend on foliage size (Niklas 1991b(Niklas , 1992a(Niklas , 1992b(Niklas , 1996.…”
Section: Light Effects On Foliage Mechanical Propertiesmentioning
confidence: 94%
See 2 more Smart Citations
“…Thus, changes in the thickness of foliage elements with irradiance were the primary determinants of modifications in EI. Ample evidence from previous studies demonstrates that petiole flexural stiffness scales positively with lamina load and petiole length, but also that both E and I may depend on foliage size (Niklas 1991b(Niklas , 1992a(Niklas , 1992b(Niklas , 1996.…”
Section: Light Effects On Foliage Mechanical Propertiesmentioning
confidence: 94%
“…Given that the largest portion of the effective second moment of area of the lamina may be attributable to major veins, our approach to determine I L may have led to an overestimation of effective E L . Nevertheless, previous investigations have demonstrated that the flexural stiffness of the major veins separated from the rest of the lamina is considerably lower than that of the petioles of similar shape and size (Niklas 1991b), indicating that embedding of veins in the lamina matrix significantly increases the composite leaf elastic modulus.…”
Section: Morphological Measurementsmentioning
confidence: 98%
See 1 more Smart Citation
“…Sclerenchyma is best defined by its mechanical function, but providing hardness is only one of its possible mechanical roles, demonstrated, for example, in the tips of thorns. More widely important is the provision of rigidity and both tensile and shear strength in plant stems (Niklas, 1991). See also: Plant Biomechanics…”
Section: Functions and Cell Typesmentioning
confidence: 99%
“…In sclerenchyma an equally important function of lignification is to attach the cells to one another and so stabilise the mechanical architecture of the plant. For example the sclerenchymatous ring in cereal straw (Travis et al, 1996) and other plant stems (Niklas, 1991) is well adapted for stiffness under the bending stress of wind, while in vines a central location for the sclerenchma combines strength in tension with flexibility in bending. Parallel isolated strands of sclerenchyma in grass leaves combine some flexibility with shear strength, influencing grazing by herbivores (Vincent, 1991).…”
Section: Cell Wall Formationmentioning
confidence: 99%